Anxious people : a novel - Backman, Fredrik, 1981- (Atria Books, 2020)
Taken hostage by a failed bank robber while attending an open house, eight anxiety-prone strangers--including a redemption-seeking bank director, two couples who would fix their marriages, and a plucky octogenarian--discover their unexpected common traits.